Technological change and price effects in agriculture: conceptual and comparative perspectives - Gabre-Madhin, Eleni Zaude; Barrett, Christopher B.; Dorosh, Paul A. (International Food Policy Research Institute, 2003)
The importance of technological advance to economic growth has become accepted fact. Yet the answers to questions of who adopts new technologies, how quickly, and at what cost to society remain elusive. While these issues are not unique throughout history, the advent of biological and chemical technologies that are both divisible and scale-neutral and the experiences referred to as the Green Revolution in the latter-half of the twentieth century throughout much of Asia have fostered a lively and long debate on the growth and particularly the distributional consequences of technological change in the agriculture of developing countries. The distributional consequences of technological change on technology adopters resulting from changes in relative output prices are an important dimension of this evolving debate. As output expands through technological change, in the face of relatively inelastic demand, the significant drop in output prices that results not only adversely affects the incomes of technology adopters but also threatens the very process